A Systematic Review of Outcome Measures in Music Therapy. Issue 1 (11th November 2017) - Spiro, Neta; Tsiris, Giorgos; Cripps, Charlotte
Abstract: Assessment, in its different guises and forms, has been a core consideration of music therapy work since the early stages of the discipline. Practitioners have devised assessment tools for different purposes such as outcome measurement. Although an increased number of tools have been published, many do not seem to be used widely in either practice or research. This situation might be connected to limited accessibility to such tools and/or the lack of centralized sources of information about them. This systematic review focuses on 26 music-therapy-specific outcome measures and identifies trends and gaps in their characteristics. The results show that most measures concern work with people with autism, developmental and learning disabilities, and special needs. Most measures have been designed using pilot studies, and most original sources introducing the measures have been published since 2000 and in journal publications. Validation processes are reported in less than half of the original sources. Most measures employ observational ratings and checklists as their data collection method and have five main categories of focus: musical engagement, functioning, communication and/or interaction, relationship, and music therapy process.